2015
DOI: 10.3171/2015.3.peds14521
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive screening for intracranial hypertension in children with acute, severe traumatic brain injury

Abstract: OBJECT The aim of this study was to determine the relationship between transcranial Doppler (TCD) derived pulsatility index (PI), end diastolic flow velocity (Vd), and intracranial pressure (ICP). The subjects in this study were 36 children admitted after severe traumatic brain injury (TBI) (postresuscitation Glasgow Coma Scale ≤ 8) undergoing invasive ICP monitoring. METHODS Subjects underwent a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 32 publications
1
41
0
2
Order By: Relevance
“…The use of diastolic FV as a relevant parameter is currently thriving in clinical practice, especially in intensive care. Authors have reported a reduction of CPP by rising ICP or decreasing systemic blood pressure in TBI (Trabold, Meyer, Blanot, Carli, & Orliaguet, ; Bouzat et al, ; O'Brien, Maa, & Reuter‐Rice, ; Ziegler, Cravens, Poche, Gandhi, & Tellez, ).…”
Section: Basic Methodsmentioning
confidence: 99%
“…The use of diastolic FV as a relevant parameter is currently thriving in clinical practice, especially in intensive care. Authors have reported a reduction of CPP by rising ICP or decreasing systemic blood pressure in TBI (Trabold, Meyer, Blanot, Carli, & Orliaguet, ; Bouzat et al, ; O'Brien, Maa, & Reuter‐Rice, ; Ziegler, Cravens, Poche, Gandhi, & Tellez, ).…”
Section: Basic Methodsmentioning
confidence: 99%
“…Although the use of TCD in pediatric TBI is still considered experimental and it is not part of the standard of care, there is a growing body of literature. Most recent studies conducted using TCD in pediatric TBI have primarily focused on its use in the diagnosis of increased intracranial pressure, cerebral vasospasm, or hyperemia and trending of cerebral flow velocities (LaRovere & O’Brien, 2015; LaRovere, O’Brien & Tasker, 2015; O’Brien, Maa, Reuter-Rice, 2015; O’Brien, Maa, Yeates, 2015; O’Brien, Reuter-Rice, Khanna, Peterson & Quinto, 2010). …”
Section: Transcranial Doppler Ultrasoundmentioning
confidence: 99%
“…Yet when Figaji and his team examined the use of a PI of one to better predict increased ICP in children with severe TBI, they found PIs were unreliable non-invasive indicators. In a recent study PIs in children with severe TBI who had a PI threshold > 1.31 in the first 24 hours after injury had a higher association of increased ICP; thereafter, PI was not a trusted measure to solely manage ICP (O’Brien, Maa, & Reuter-Rice, 2015). …”
Section: Transcranial Doppler Ultrasoundmentioning
confidence: 99%
“…To date, however, the published reports regarding the utility of these non-invasive techniques – particularly in children with severe TBI - have been limited. A recent report by O’Brien and colleagues demonstrated reasonable sensitivity and specificity of pulsatility index from the middle cerebral artery (measured by tCD) with intracranial hypertension - although the technique was not accurate enough to predict actual ICP values [5]. Similarly, Gwer and colleagues demonstrated some utility with the tympanic membrane displacement analyzer in comatose children from Kenya and children in idiopathic intracranial hypertension clinic in the UK [6].…”
mentioning
confidence: 99%